Management of Prosthesis Embolization into Left Ventricle after Transcatheter Aortic Valve Implantation: A Case Report - Süleyman Yazıcı; Nihan Kayalar; Mehmed Yanartaş; Hasan Tezcan; Osman Fehmi Beyazal (Düzce Tıp Fakültesi Dergisi)
Transcatheter aortic valve implantation is recommended in advanced aortic stenosis, in elderly patients who are not suitable for surgery. Valve embolization is one of the most important complications that is life-threatening. A 61-year-old male patient was being followed up with a complaint of shortness of breath. He had a history of coronary artery bypass graft operation. Transthoracic echocardiography revealed severe aortic stenosis. Transfemoral transcatheter aortic valve implantation was performed, but while the balloon passed through the valve, the valve embolized the ventricle. The patient was then taken into operation. The native aortic valve was resected, the valve embolized into the ventricle was cut and removed, and surgical aortic valve replacement was performed. Endovascular methods can be preferred in suitable patients, but in cases where they fail, urgent open-heart surgery is required. One of the most important points is that the guidewire should not be removed when embolization.